PENGGUNAAN CAMPUR KODE BAHASA SASAK KE BAHASA ARAB DALAM KOMUNIKASI DI ASRAMA MA’HAD HIKMATUSYSYARIEF - Syarifah & Like Raskova Octaberlina (Universitas Islam Malang, 2021)
Abstract: This study discusses the use of mixed Sasak language codes into Arabic in communicating in dormitories. In this study, researchers found that there are two types of mixed code used by students in Ma'had Hikmatusysyarief in communicating daily, namely, mixing code outward (outer code mixing) and mixing code into (inner code mixing). And there are two forms of mixed code the first, sasak code to Arabic code, the second Indonesian code to Sasak code. The method that researchers use is the listening method, . This method of hearing (see) can be the same as observation or observation if in social sciences. Researchers conducted direct observations at Ma'had Hikmatusysyarief dormitory, Narmada West Lombok. With data collection, have conversations with respondents. The method in this study also used fishing methods, researchers lured informants to speak.Keywords: Code Mix, Sasak Language, Arabic